Art and the Sea. - Roberts, Emma (Liverpool University Press, 2022)
'An original and significant volume of fresh research and new interpretations in a multi-disciplinary field of study, this important text promotes the dynamic interaction of maritime and artistic approaches to the past, providing new methodologies, insights and options for the future.' Professor Andrew Lambert, King's College London This edited collection re-examines the relationship between art and the sea, reflecting growing interest in the intersections between art and maritime history. Artists have always been fascinated by and drawn to the sea and this book considers some of the themes and approaches in art that have evolved as a result of this captivation. The chapters consider how an examination of art can provide new insights into existing knowledge of port and maritime history, and are representative of a 'cultural turn' in port and maritime studies, which is becoming increasingly visible. In Art and the Sea, multiple perspectives are offered as a result of the contributor... Publisher description.
Description based upon print version of record.
Keywords: Navigation -- History.; Marine art.; Navigation -- Histoire.; Marines (Art); seascapes.; Maritime history.; Navigation; The arts: general issues.; Art and Design.; ports; Cultural Turn; art; maritime; travel; nostalgia; Imperialism; sea; nationalism; colonialism; painting; History